A review of nature-based solutions for urban water management in European circular cities: a critical assessment based on case studies and literature. Issue 1 (3rd January 2020) - Oral, Hasan Volkan; Carvalho, Pedro; Gajewska, Magdalena; Ursino, Nadia; Masi, Fabio; Hullebusch, Eric D. van; Kazak, Jan K.; Exposito, Alfonso; Cipolletta, Giulia; Andersen, Theis Raaschou; Finger, David Christian; Simperler, Lena; et al.
Abstract: Nature-based solutions (NBS) can protect, manage and restore natural or modified ecosystems. They are a multidisciplinary, integrated approach to address societal challenges and some natural hazards effectively and adaptively, simultaneously providing human well-being and biodiversity benefits. NBS applications can be easily noticed in circular cities, establishing an urban system that is regenerative and accessible. This paper aims to offer a review on NBS for urban water management from the literature and some relevant projects running within the COST Action 'Implementing nature-based solutions for creating a resourceful circular city'. The method used in the study is based on a detailed tracking of specific keywords in the literature using Google Scholar, ResearchGate, Academia.edu, ScienceDirect and Scopus. Based on this review, three main applications were identified: (i) flood and drought protection; (ii) the water-food-energy nexus; and (iii) water purification. The paper shows that NBS provide additional benefits, such as improving water quality, increasing biodiversity, obtaining social co-benefits, improving urban microclimate, and the reduction of energy consumption by improving indoor climate. The paper concludes that a systemic change to NBS should be given a higher priority and be preferred over conventional water infrastructure.